2014
DOI: 10.1093/pcp/pcu117
|View full text |Cite
|
Sign up to set email alerts
|

A Cd/Fe/Zn-Responsive Phytochelatin Synthase is Constitutively Present in the Ancient Liverwort Lunularia cruciata (L.) Dumort

Abstract: Lunularia cruciata occupies a very basal position in the phylogenetic tree of liverworts, which in turn have been recognized as a very early clade of land plants. It would therefore seem appropriate to take L. cruciata as the startingpoint for investigating character evolution in plants' metal(loid) response. One of the strongest evolutionary pressures for land colonization by plants has come from potential access to much greater amounts of nutritive ions from surface rocks, compared to water. This might have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 47 publications
7
31
0
Order By: Relevance
“…During that time, however, an increase of GSH content, primarily under Cd treatment, could be observed. The findings of this study and the studies performed by Carginale et al (2004) and Degola et al (2014) showed that intracellular Cd is primarily stored in the vacuoles of bryophyte cells. Here, high amounts of S and P were also observed, which led to the conclusion that one of the dominant mechanisms of bryophyte tolerance to heavy metals, at least to Cd, is the formation of cytoplasmatic GSH/Cd complexes and their subsequent transport into vacuoles, where they can be degraded and the Cd accumulated as phosphate.…”
Section: Mechanisms Of Bryophyte Resistance To Heavy Metal Pollutionsupporting
confidence: 84%
See 4 more Smart Citations
“…During that time, however, an increase of GSH content, primarily under Cd treatment, could be observed. The findings of this study and the studies performed by Carginale et al (2004) and Degola et al (2014) showed that intracellular Cd is primarily stored in the vacuoles of bryophyte cells. Here, high amounts of S and P were also observed, which led to the conclusion that one of the dominant mechanisms of bryophyte tolerance to heavy metals, at least to Cd, is the formation of cytoplasmatic GSH/Cd complexes and their subsequent transport into vacuoles, where they can be degraded and the Cd accumulated as phosphate.…”
Section: Mechanisms Of Bryophyte Resistance To Heavy Metal Pollutionsupporting
confidence: 84%
“…More importantly, it has also been found that most of the intracellular Cd is bound to the thiol-rich compounds of similar weight such as phytochelatins, indicating that, as in other plants, these compounds may constitute the principal mechanism for heavy metal sequestration. Further, Degola et al (2014) have unambiguously confirmed that the compounds found in the L. cruciata are phytochelatins and that some of them (such as PC2) may constantly be present in bryophyte cells managing the homeostasis of the micronutrients. However, testing the effects of different heavy metals on the induction of phytochelatin synthesis, and comparing the results of this study with those from a study of Arabidopsis thaliana (L.) Heynh., led to the conclusion that bryophyte PCs and their synthases have a narrower function, involved only in the regulation of the Fe/Zn homeostasis and detoxification of Cd.…”
Section: Mechanisms Of Bryophyte Resistance To Heavy Metal Pollutionmentioning
confidence: 76%
See 3 more Smart Citations